2000
DOI: 10.1161/01.cir.101.25.2935
|View full text |Cite
|
Sign up to set email alerts
|

Active Remodeling of the Coronary Arterial Lesions in the Late Phase of Kawasaki Disease

Abstract: Active remodeling of the coronary artery lesions in Kawasaki disease continues in the form of luxuriant intimal proliferation and neoangiogenesis for several years after the onset of the disease. This process is distinct from adult-onset atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 14 publications
13
124
0
2
Order By: Relevance
“…In fact, pathological studies have revealed that CAL in KD are characterized by subendothelial oedema, vascular EC damage and the infiltration of inflammatory cells [21,22]. On the other hand, an active remodeling process has been reported to occur in the CAL of acute KD [14,15] which thereafter continues several years after the onset of KD [16]. VEGF can recruit endothelial progenitor cells from the bone marrow into the peripheral circulation [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, pathological studies have revealed that CAL in KD are characterized by subendothelial oedema, vascular EC damage and the infiltration of inflammatory cells [21,22]. On the other hand, an active remodeling process has been reported to occur in the CAL of acute KD [14,15] which thereafter continues several years after the onset of KD [16]. VEGF can recruit endothelial progenitor cells from the bone marrow into the peripheral circulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix matalloproteinases (MMP)-2 and -9 were expressed at the CAL in KD, thus suggesting that angiogenesis occurs in the remodeling process of the arterial walls in acute KD vasculitis [15]. Furthermore, an immunohistochemical study demonstrated that intimal proliferation and neoangiogenesis are accompanied by an over-expression of VEGF at the CAL in the late phase of KD [16]. Although the serum levels of VEGF have been reported to increase in the acute phase of KD [17,18], there has so far been no report on the serum levels of ES in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several growth factors are prominently expressed at the inlet and outlet of aneurysms, where they are activated by high shear stress. 57 During the clinical course of Kawasaki disease, vomiting and abdominal pain are seen often. Kurashige and colleagues described the intestinal tract in 31 fatal cases, but in only 3 patients was mesenteric arteritis found.…”
Section: Pathologymentioning
confidence: 99%
“…Aneurysms also may regress to normal internal lumen diameter over time; optimal management of patients with regressed aneurysms is controversial because structural and functional coronary artery abnormalities persist. 57,126,226,235,236 The fol-lowing suggestions for long-term management are based on a consensus of experts and serve as a guide to clinicians until long-term studies and prospective trials facilitate evidencebased practice (evidence level C).…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Increased TGF-␤1 protein expression is found in the coronary smooth muscle cells in patients with KD. 34,35 However, although one study 36 found that serum levels of TGF-␤1 were increased in patients with acute KD compared with febrile controls, another study 37 documented that levels were decreased. Therefore, the role that TGF-␤ plays in the pathogenesis of inflammatory arteritis, such as KD, remains unclear.…”
Section: Discussionmentioning
confidence: 99%